The leaky corporation. (Economist, 2011)
The article examines confidential communications within corporations. A series of embarrassing public disclosures of information about major corporations is noted. The difficulty of maintaining confidentiality due to the digitization of information is considered. Computer security software being marketed to corporations is discussed. A study indicated that efforts to limit employee access to information can result in lower corporate profits by hindering decision making is considered.